PENERAPAN PENDEKATAN RULE OF REASON TERHADAP PERSEKONGKOLAN TENDER BERDASARKAN UNDANG-UNDANG NO. 5 TAHUN 1999 TENTANG LARANGAN PRAKTIK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT - Sabrena Sukma; Rika Lestari; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Business conspiracy or conspiracy is a form of cooperation carried out by businessactors with other business actors with the intention of controlling the relevant market forthe interests of the conspiring business actors. The Business Competition SupervisionCommission (KPPU) is tasked with examining alleged violations of Law Number 5 of1999 concerning the Prohibition of Monopolistic Practices and Unfair BusinessCompetition, and each decision uses a Per Se Illegal approach and a Rule of Reasonapproach. In the case of tender conspiracy, the Commission Council must apply the Ruleof Reason approach in its decision to analyze the case. However, the KPPU's decisionhas not been consistent in applying the Rule of Reason approach to the case of tenderconspiracy by the government. Therefore, the research objectives of this thesis are,firstly, to determine the variation of the application of the Rule of Reason approach to theKPPU's decision on the procurement of goods/services by the government. Second, tofind out the ideal indicators in the application of the Rule of Reason approach to theKPPU's decision. This study uses normative/legal research methods to analyze casestudies. This study uses secondary data sources by using primary legal materials,secondary legal materials, and tertiary legal materials. From the results of the studythere are 2 main things that can be concluded. First, the variation of the application ofthe Rule of Reason approach to the KPPU's decision on the procurement ofgoods/services by the government is contained in Decision Number 04/KPPU-L/2020,Decision Number 05/KPPU-I/2020 and Decision Number 35/KPPU-I/2020. Where in thedecision Number 04/KPPU-L/2020 and Decision No.05/KPPU-I/2020 the Rule of Reasonapproach has not been implemented perfectly, and in Decision Number 35/KPPU-I/2020the Rule of Reason approach has been implemented perfectly. Second, the ideal indicatorto apply the Rule of Reason approach is regulated in Article 22 of the 1999 Law on theProhibition of Conspiracy, which regulates indications of conspiracy in tenders. Indecision Number 04/KPPU-L/2020 the Commission Council did not apply the Rule ofReason approach perfectly. In decision Number 05/KPPU-I/2020 the CommissionCouncil has not implemented the Rule of Reason approach perfectly. In decision Number35/KPPU-I/2020 The Commission application of the Rule of Reason has been perfect.Keywords: Rule Of Reason Approach, Tender Conspiracy, KPPU